2004
DOI: 10.1016/j.ijpara.2003.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of TNF in limiting liver pathology and promoting parasite survival during schistosome infection

Abstract: CD4 + T cell responses and macrophage activation are essential components of schistosome egginduced granuloma formation. Previous studies implicated tumour necrosis factor (TNF) as a potential mediator of macrophage recruitment and activation during schistosome infection. Here we demonstrate that signalling by TNF and its receptors can influence granuloma formation, but is ultimately dispensable for granuloma formation in this system. However, we identify a previously unrecognised role for TNF in limiting hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 38 publications
2
38
0
1
Order By: Relevance
“…In a spontaneous mouse model of insulin-dependent diabetes mellitus, the NOD mouse, TNF led to increased [26,27] or attenuated [28][29][30] islet infiltration, depending on timing and duration of exposure of the immune system to TNF [11]. Indications for an immunoregulatory role for TNF have been also reported in mouse models of infectious diseases, such as in schistosome [31] and M. tuberculosis/BCG infections [32], where TNF was found to be required to limit immunopathologies in the liver and lung, respectively. In humans, anti-inflammatory effects of TNF may be responsible for the unexpected failure of treating patients with multiple sclerosis with a soluble TNFR1 fusion protein (lenercept) [33].…”
Section: Discussionmentioning
confidence: 87%
“…In a spontaneous mouse model of insulin-dependent diabetes mellitus, the NOD mouse, TNF led to increased [26,27] or attenuated [28][29][30] islet infiltration, depending on timing and duration of exposure of the immune system to TNF [11]. Indications for an immunoregulatory role for TNF have been also reported in mouse models of infectious diseases, such as in schistosome [31] and M. tuberculosis/BCG infections [32], where TNF was found to be required to limit immunopathologies in the liver and lung, respectively. In humans, anti-inflammatory effects of TNF may be responsible for the unexpected failure of treating patients with multiple sclerosis with a soluble TNFR1 fusion protein (lenercept) [33].…”
Section: Discussionmentioning
confidence: 87%
“…Eosinophils can cause parasite damage in S. mansoni and other worm infections in vitro (26) and in vivo (34). Nevertheless, mice selectively deficient in eosinophils (31) or in IL-5, which causes a profound reduction of eosinophils, control parasite burden as efficiently as wild-type mice (28,30).…”
Section: Discussionmentioning
confidence: 99%
“…This process also indirectly induces the production of other fibrogenic factors, such IL-1 and IL-6 (Kimura et al 2003). Moreover, Davies et al (2004) have reported that TNF-α essentially functions as a trophic factor for maintaining the viability of adult Schistosoma worms, in addition to its role as a mitogen and promoter of tumour development in schistosomiasis-associated carcinoma (Balkwill et al 2006).…”
Section: Resultsmentioning
confidence: 99%